The effect of simulation training on the counseling skills of nutritional science students in dietetic internships - Ifat Linder; Zafit Lukach; Keren Pergament; Rafi Steckler; Sigal Tepper (BMC Medical Education)
Abstract Simulations are a common tool in training aircrews, medical personnel and educators, providing experience in scenarios from the relevant content area and expanding the range of responses that simulation participants can acquire before they enter the field. Simulations have also been used in dietetic internships to improve clinical counseling skills. However, the use of structured simulations that involve progressive, multisession patient interactions has not been extensively studied in the context of dietetic internships. This study employed consecutive scenario models where interns developed ongoing interactions with the same simulated patient over multiple sessions, representing a significant methodological innovation in the field. A mixed method methodology was used to analyze closed and open-ended questionnaires which were administered to twenty-one interns, simulation actors and professional dietitians. This pilot study demonstrates the effectiveness of group and individual simulation training in enhancing dietetic interns’ counseling skills during their training and describes how simulation can contribute to both the professional skills and self-efficacy required to lead a counseling session. These findings will enable additional academic departments to examine the integration of simulation into the training programs of interns in tracks that include a practicum.